PENGAMBILAN KEPUTUSAN STRATEGIS KEPALA SMK NEGERI 1 TOLITOLI - Fariha, Fariha (Pascasarjana Universitas Negeri Makassar, 2017)
Strategic decisions are very important decisions and determinants of organizational success in the future. Therefore, the formulation of the problem in this study is (1) the principal's strategic decision-making process, (2) supporting and inhibiting factors in strategic decision making. This study uses a qualitative approach with data collection techniques through observation, interviews and documentation. The results of the study show that strategic decision making is done by identifying problems, development, completion and implementation and evaluation. Most of the strategic decision making was coordinated first with the vice principals, teachers before being defined as a program in planning. This provides an important role for deputy principals as assistants to school principals in managing their institutions systematically as well as teachers as part of the school organization.